Find the principal solutions of each of the following equations:
(i)
(ii)
(iii)
(iv)
(v)
(vi)
To Find: Principal solution.
[NOTE: The solutions of a trigonometry equation for which 0x
2
is called principal solution]
(i) Given:
Formula used: sin = sin
= n
+ (-1)n
, n
I
By using above formula, we have
= sin
x = n
+
(-1)n
Put n= 0 x = 0
+
(-1)0
x =
Put n= 1 x = 1
+
(-1)1
x =
1
x =
=
So principal solution is x= and
(ii) Given:
Formula used: cos = cos
= 2n
, n
I
By using above formula, we have
= cos
= 2n
, n
I
Put n= 0 x = 2n
x =
Put n= 1 x = 2
x =
,
x =
,
[ 2
So it is not include in principal solution]
So principal solution is x= and
(iii) Given:
Formula used: tan = tan
= n
, n
I
By using above formula, we have
= tan
x = n
, n
I
Put n= 0 x = n
x =
Put n= 1 x =
x =
x =
So principal solution is x= and
(iv) Given:
We know that tan cot
= 1
So cotx = tanx =
The formula used: tan = tan
= n
, n
I
By using the above formula, we have
tanx = = tan
= n
, n
I
Put n= 0 x = n
x =
Put n= 1 x =
x =
So principal solution is x= and
(v) Given: cosec x = 2
We know that cosec sin
= 1
So sinx =
Formula used: sin = sin
= n
+ (-1)n
, n
By using above formula, we have
sinx = = sin
= n
+
(-1)n
Put n= 0 = 0
+
(-1)0
=
Put n= 1 = 1
+
(-1)1
=
1
=
=
So principal solution is x= and
(vi) Given: sec x =
We know that sec cos
= 1
So cosx =
Formula used: cos = cos
= 2n
, n
I
By using the above formula, we have
cosx = = cos
x = 2n
, n
I
Put n= 0 x = 2n
x =
Put n= 1 x = 2
x =
,
x =
,
[ 2
So it is not include in principal solution]
So principal solution is x= and
Find the principal solutions of each of the following equations :
(i)
(ii)
(iii) tan x = -1
(iv)
(v)
(vi)
To Find: Principal solution.
(i) Given:
Formula used: sin = sin
= n
+ (-1)n
, n
I
By using above formula, we have
= -sin
= sin(
= sin
x = n
+
(-1)n
Put n= 0 x = 0
+
(-1)0
x =
Put n= 1 x = 1
+
(-1)1
x =
1
x =
=
[ NOTE: =
]
So principal solution is x= and
(ii) Given: cosx =
Formula used: cos = cos
= 2n
, n
I
By using above formula, we have
cosx = = cos
x = 2n
, n
I
Put n= 0 x = 2 × 0 ×
x =
Put n= 1 x = 2
x =
,
x =
,
[ 2
So it is not include in principal solution]
So principal solution is x= and
(iii) Given: tan x = -1
Formula used: tan = tan
= n
, n
I
By using above formula, we have
tan x = -1 = tan x = n
, n
I
Put n= 0 x = n
x =
Put n= 1 x =
x =
x =
So principal solution is x= and
(iv) Given: cosec x =
We know that cosec sin
= 1
So sinx =
Formula used: sin = sin
= n
+ (-1)n
, n
By using above formula, we have
sinx = = sin
= n
+
(-1)n
Put n= 0 x = 0
+
(-1)0
x =
Put n= 1 x = 1
+
(-1)1
x =
1
x =
=
[ NOTE: =
]
So principal solution is x= and
(v) Given: tan x = -
Formula used: tan = tan
= n
, n
I
By using above formula, we have
tan x = - = tan
x = n
, n
I
Put n= 0 x = n
x =
Put n= 1 x =
x =
So principal solution is x= and
(vi) Given: sec x =
We know that sec cos
= 1
So cosx =
Formula used: cos = cos
= 2n
, n
I
By using the above formula, we have
cosx = = cos
x = 2n
, n
I
Put n= 0 x = 2n
x =
Put n= 1 x = 2
x =
,
x =
,
[ 2
So it is not include in principal solution]
So principal solution is x= and
Find the general solution of each of the following equations:
(i) sin 3x = 0
(ii)
(iii)
(iv) cos 2x = 0
(v)
(vi)
(vii) tan 2x = 0
(viii)
(ix)
To Find: General solution.
[NOTE: A solution of a trigonometry equation generalized by means of periodicity, is known as general solution]
(i) Given: sin 3x = 0
Formula used: sin= 0
= n
, n
I
By using above formula, we have
sin 3x = 0 3x = n
x =
where n
I
So general solution is x= where n
I
(ii) Given: sin = 0
Formula used: sin= 0
= n
, n
I
By using above formula, we have
sin = 0
= n
x =
where n
I
So general solution is x= where n
I
(iii) Given: sin = 0
Formula used: sin= 0
= n
, n
I
By using the above formula, we have
sin = 0
= n
x = n
-
where n
I
So general solution is x= n-
where n
I
(iv) Given: cos 2x = 0
Formula used: cos= 0
= (2n+1)
, n
I
By using above formula, we have
cos 2x = 0 2x = (2n+1)
x = (2n+1)
where n
I
So general solution is x= (2n+1)where n
I
(v) Given: cos = 0
Formula used: cos= 0
= (2n+1)
, n
I
By using the above formula, we have
cos = 0
= (2n+1)
x = (2n+1)
where n
I
So general solution is x= (2n+1)where n
I
(vi) Given: cos = 0
Formula used: cos= 0
= (2n+1)
, n
I
By using the above formula, we have
cos = 0
= (2n+1)
x = (2n+1)
-
x = n
+
where n
I
So general solution is x= n +
where n
I
(vii) Given: tan 2x = 0
Formula used: tan= 0
= n
, n
I
By using above formula, we have
tan 2x = 0 2x = n
x =
where n
I
So general solution is x= where n
I
(viii) Given: tan = 0
Formula used: tan= 0
= n
, n
I
By using above formula, we have
tan = 0
= n
3x = n
-
x =
-
where n
I
So general solution is x = -
where n
I
(ix) Given: tan = 0
Formula used: tan= 0
= n
, n
I
By using above formula, we have
tan = 0
= n
2x = n
-
x =
+
where n
I
So general solution is x = +
where n
I
Find the general solution of each of the following equations:
(i)
(ii) cos x = 1
(iii)
To Find: General solution.
(i) Given: sin x =
Formula used: sin = sin
= n
+ (-1)n
, n
I
By using above formula, we have
sin x = = sin
x = n
+ (-1)n .
So general solution is x = n + (-1)n .
where n
I
(ii) Given: cos x = 1
Formula used: cos = cos
= 2n
, n
I
By using above formula, we have
cos x = 1= cos(0)
x = 2n
, n
I
So general solution is x = 2n where n
I
(iii) Given: sec x =
We know that sec cos
= 1
So cosx =
Formula used: cos = cos
= 2n
, n
I
By using above formula, we have
cosx = = cos
x = 2n
, n
I
So general solution is x = 2n where n
I
Find the general solution of each of the following equations:
(i)
(ii)
(iii) tan x = -1
To Find: General solution.
(i) Given: cos x =
Formula used: cos = cos
= 2n
, n
I
By using above formula, we have
cos x = =
cos(
)= cos(
)=cos(
)
x = 2n
, n
I
So general solution is x = 2n where n
I
(ii) Given: cosec x =
We know that cosec sin
= 1
So sinx =
Formula used: sin = sin
= n
+ (-1)n
, n
By using above formula, we have
sinx = = sin
x = n
+
(-1)n.
So general solution is x = n +
(-1)n.
where n
I
(iii) Given: tan x = -1
Formula used: tan = tan
= n
, n
I
By using above formula, we have
tan x = -1= tan x = n
, n
I
So the general solution is x = nwhere n
I
Find the general solution of each of the following equations:
(i)
(ii)
(iii)
To Find: General solution.
(i) Given: sin 2x =
Formula used: sin = sin
= n
+ (-1)n
, n
I
By using above formula, we have
sin 2x = = sin
2x = n
+ (-1)n .
x =
+ (-1)n .
, n
I
So general solution is x = + (-1)n .
where n
I
(ii) Given: cos 3x =
Formula used: cos = cos
= 2n
, n
I
By using above formula, we have
cos 3x = = cos(
)
3x = 2n
x =
, n
I
So the general solution is x = where n
I
(iii) Given: tan =
Formula used: tan = tan
= n
, n
I
By using above formula, we have
tan =
= tan
= n
x =
, n
I
So general solution is x =(3n+1),where n
I
Find the general solution of each of the following equations:
(i) sec 3x = -2
(ii) cot 4x = -1
(iii)
To Find: General solution.
(i) Given: sec 3x = -2
We know that sec cos
= 1
So cos 3x =
Formula used: cos = cos
= 2n
, n
I
By using above formula, we have
cos 3x = = -cos
= cos
= cos
3x = 2n
x =
, n
I
So the general solution is x = , ,where n
I
(ii) Given: cot 4x = -1
We know that tan cot
= 1
So tan 4x = -1
Formula used: tan = tan
= n
, n
I
By using above formula, we have
tan 4x = -1= tan 4x = n
x =
, n
I
So general solution is x = (4n+3) ,where n
I
(iii) Given: cosec 3x =
We know that cosec sin
= 1
So sin 3x =
Formula used: sin = sin
= n
+ (-1)n.
, n
I
By using above formula, we have
sin 3x = = sin
3x= n
+
(-1)n .
x=
+
(-1)n .
, n
I
So general solution is x = +
(-1)n .
, where n
I
Find the general solution of each of the following equations:
(i) 4cos2 x = 1
(ii) 4sin2 x – 3 = 0
(iii) tan2 x = 1
To Find: General solution.
(i) Given: 4cos2 x = 1 cos2 x =
cos2 x = cos2
Formula used: cos2 = cos2
= n
, n
I
By using the above formula, we have
x = n , n
I
So the general solution is x = n where n
I
(ii) Given: 4sin2 x – 3 = 0 sin2 x =
= sin2
sin2 x = sin2
Formula used: sin2 = sin2
= n
, n
I
By using the above formula, we have
x = n , n
I
So the general solution is x = n where n
I
(ii) Given: tan2 x = 1 tan2 x = tan2
tan2 x = tan2
The formula used: tan2 = tan2
= n
, n
I
By using the above formula, we have
x = n , n
I
So the general solution is x = n where n
I
Find the general solution of each of the following equations:
(i) cos 3x = cos 2x
(ii) cos 5x = sin 3x
(iii) cos mx = sin nx
To Find: General solution.
(i) Given: cos 3x = cos 2x cos 3x - cos 2x = 0
-2sin
sin
= 0
[NOTE: cos C – cos D = -2sin sin
]
So, sin = 0 or sin
= 0
Formula used: sin = 0
= n
, n
I
= n
or
= m
where n, m
I
x = 2 n/5 or x = 2m
where n, m
I
So general solution is x = 2 n/5 or x = 2m
where n, m
I
(ii) Given: cos 5x = sin 3x cos 5x = cos
Formula used: cos = cos
= 2n
, n
I
By using the above formula, we have
5x = 2n or 5x = 2n
8x = 2n or 2x = 2n
x = or x = n
where n
I
So general solution is x = or x = n
where n
I
(iii) Given: cos mx = sin nx cos mx = cos
Formula used: cos = cos
= 2k
, k
I
By using the above formula, we have
mx = 2k or 5x = 2k
(m+n)x = 2k or (m-n)x = 2k
x = or x =
where k
I
x = or x =
where k
I
So the general solution is x = or x =
where k
I
Find the general solution of each of the following equations:
sin x = tan x
To Find: General solution.
Given: sin x = tan x sin x = sin x
cos x
So sin x = 0 or cos x = 1 = cos(0)
Formula used: sin= 0
= n
, n
I and cos
= cos
= 2k
, k
I
x = n or x = 2k
where n, k
I
So general solution is x =n or x = 2k
where n, k
I
Find the general solution of each of the following equations:
4sin x cos x + 2sin x + 2cos x + 1 = 0
To Find: General solution.
Given: 4sin x cos x + 2sin x + 2cos x + 1 = 0 2sin x(2cos x + 1) + 2cos x + 1 = 0
So (2cos x + 1)( 2sin x + 1) = 0
cos x = = cos(
) or sin x =
= sin
Formula used: cos = cos
= 2n
or sin
= sin
= m
+ (-1)m
where n,m
I
x = 2n or x = m
+
(-1)m .
where n, m
I
So the general solution is x =2n or x = m
+
(-1)m .
where n, m
I
Find the general solution of each of the following equations:
sec2 2x = 1- tan 2x
To Find: General solution.
Given: sec2 2x = 1- tan 2x 1 + tan22x+ tan 2x = 1
tan 2x (1+tan 2x) = 0
So, tan 2x = 0 or tan 2x = -1 = tan ()
Formula used: : tan= 0
= n
, n
I and tan
= tan
= k
, k
I
By using above formula, we have
2x = n or 2x = k
x =
or x =
So the general solution is x = or x =
where n, k
I
Find the general solution of each of the following equations:
tan3 x – 3tan x = 0
To Find: General solution.
Given: tan3 x – 3tan x = 0 tan x(tan2 x – 3) = 0
tan x = 0 or tanx =
tan x = 0 or tanx = tan(
) or tan x = tan(
)
Formula used: tan
= 0
= n
, n
I, tan
= tan
= k
, k
I
So x = n or x = k
+
or x = p
+
where n, k, p
I
So general solution is x = n or x = k
+
or x = p
+
where n, k, p
I
Find the general solution of each of the following equations:
sin x + sin 3x + sin 5x = 0
To Find: General solution.
Given: sin x + sin 3x + sin 5x = 0 sin 3x + 2sin 3x cos 2x= 0
sin 3x (1 + 2cos 2x) = 0
[NOTE: sin C + sin D = 2sin (C+D)/2 × cos (C-D)/2]
sin 3x = 0 or cos 2x =
= cos(
)
Formula used: sin= 0
= n
, n
I, cos
= cos
= 2k
, k
I
3x = n
or 2x = 2k
x =
or x = k
where n,k
I
So general solution is x = or x = k
where n, k,
I
Find the general solution of each of the following equations:
sin x tan x – 1 = tan x – sin x
To Find: General solution.
Given: sin x tan x – 1 = tan x – sin x sin x(tan x + 1) = tan x + 1
So sin x = 1 = sin () or tan x = -1 = tan(
)
Formula used: sin = sin
= n
+ (-1)n
, n
I and tan
= tan
= k
, k
I
x = n
+ (-1)n
or x = k
where n, k
I
So general solution is x = n + (-1)n
or x = k
where n, k,
I
Find the general solution of each of the following equations:
cos x + sin x = 1
To Find: General solution.
Given: cos x + sin x = 1 cos(x -
) =
= cos
[divide on both sides and cos(x-y) = cos x cos y - sin x sin y]
Formula used: cos = cos
= 2k
, k
I
x -
= 2k
x = 2k
+
x = 2k
+
or
x = 2k
+
x = 2k
+
or x = 2k
So general solution is x = 2n +
or x = 2n
where n
I
Find the general solution of each of the following equations:
cos x – sin x = -1
To Find: General solution.
Given: cos x - sin x = 1 cos(x +
) =
= cos
[divide on both sides and cos(x-y) = cos x cos y - sin x sin y]
So sin x = 0 or cos x = 0
Formula used: cos = cos
= 2k
, k
I
x +
= 2k
x = 2k
-
x = 2k
-
or
x = 2k
-
x = 2k
-
or x = 2k
So general solution is x = 2n +
or x = (2n-1)
where n
I
Find the general solution of each of the following equations: cos x + sin x = 1
To Find: General solution.
Given: cos x + sin x = 1
cos (x -
) =
= cos(
or cos(
)
[Divide on both sides and cos(x-y) = cos x cos y - sin x sin y]
Formula used: cos = cos
= 2n
By using above formula, we have
x -
= 2n
x = 2n
+
x = 2n
+
or x = 2n
-
where n
I
So general solution is x = 2n +
or x = 2n
-
where n
I
Find the general solution of each of the following equations:
2 tan x – cot x + 1 = 0
To Find: General solution.
Given: 2 tan x – cot x + 1 = 0 2tan2x – 1 + tan x = 0
2tan2x – 1 + 2tan x – tanx = 0
2tanx(tanx +1) – (1+ tanx) = 0
(2tanx-1) (1+ tanx) = 0
tan x =
=
or tan x = -1 = tan
Formula used: tan = tan
= n
, n
I
x = n or x = n
So the general solution is x = nor x = n
where n
I
Find the general solution of each of the following equations:
sin x tan x – 1 = tan x – sin x
To Find: General solution.
Given: sin x tan x – 1 = tan x – sin x sin x(tan x + 1) = tan x + 1
So sin x = 1 = sin () or tan x = -1 = tan(
)
Formula used: sin = sin
= n
+ (-1)n
, n
I and tan
= tan
= k
, k
I
x = n
+ (-1)n
or x = k
where n, k
I
So general solution is x = n + (-1)n
or x = k
where n, k
I
Find the general solution of each of the following equations:
cot x + tan x = 2 cosec x
To Find: General solution.
Given: cot x + tan x = 2 cosec x cos2x + sin2x = 2 sinx cosx cosec x
1 = sin 2x cosec x
cosec 2x = cosecx
sin x = sin 2x
sin x = 2 sin x cos x
sin x = 0 or cos x =
= cos(
)
Formula used: sin = 0
= n
, cos
= cos
= 2n
By using above formula , we have
x = n or x = 2m
where n, m
I
So general solution is x = n or x = 2m
where n, m
I